ANALISIS PENGARUH HAMBATAN SAMPING TERHADAP KINERJA DI JALAN LINTAS SUMATERA PULAU MARIA – TELUK DALAM, ASAHAN - Manik, Iman Setiawan; Hamzah, Amir (Universitas Asahan, 2025)
The current increase in the number of vehicles owned by the public is not in line with the growth of transportation infrastructure. This results in various problems, especially traffic congestion that is difficult for the government to overcome. In the Regency area, especially on the Trans-Sumatra Highway from Maria Island to Teluk Dalam. Market and educational activities in the area cause side obstacles that affect traffic flow. The purpose of this study was to determine the level of side obstacles and analyze their impact on the performance of the Maria Island - Teluk Dalam road. The study was conducted through a side obstacle survey to see traffic disruptions and a traffic volume survey to see the density of vehicles passing through the area. Calculations are based on the Indonesian Road Capacity Guidelines PKJI 2023 for out-of-town roads. The results show that the weight of the side obstacles that occurred on Monday/June 19, 2025 is included in the high side obstacle (ST) class with a total value of 251.6 incidents. The very high side obstacles on Monday occurred due to the large number of activities from pedestrians and pedestrians and vehicles entering and leaving the market. In contrast to Saturday and Sunday, which have the potential for moderate side obstacles, on Saturday the total value of incidents is 196 and on Sunday it is lower than Saturday with the total value of incidents reaching 171.2